Characteristics of difficult-to-treat rheumatoid arthritis: results of an international survey. Issue 12 (7th September 2018) - Roodenrijs, Nadia M T; de Hair, Maria J H; van der Goes, Marlies C; Jacobs, Johannes W G; Welsing, Paco M J; van der Heijde, Désirée; Aletaha, Daniel; Dougados, Maxime; Hyrich, Kimme L; McInnes, Iain B; Mueller-Ladner, Ulf; Senolt, Ladislav; et al.
Abstract : Objectives: Patients with difficult-to-treat rheumatoid arthritis (RA) remain symptomatic despite treatment according to current European League Against Rheumatism (EULAR) management recommendations. These focus on early phases of the disease and pharmacological management. We aimed to identify characteristics of difficult-to-treat RA and issues to be addressed in its workup and management that are not covered by current management recommendations. Methods: An international survey was conducted among rheumatologists with multiple-choice questions on disease characteristics of difficult-to-treat RA. Using open questions, additional items to be addressed and items missing in current management recommendations were identified. Results: 410 respondents completed the survey: 50% selected disease activity score assessing 28 joints >3.2 OR presence of signs suggestive of active disease as characteristics of difficult-to-treat RA; 42% selected fatigue; 48% selected failure to ≥2 conventional synthetic disease-modifying antirheumatic drugs (DMARDs) AND ≥2 biological/targeted synthetic DMARDs; 89% selected inability to taper glucocorticoids below 5 mg or 10 mg prednisone equivalent daily. Interfering comorbidities, extra-articular manifestations and polypharmacy were identified as important issues missing in current management recommendations. Conclusions: There is wide variation in concepts of difficult-to-treat RA. Several important issues regarding these patients are not addressed by current EULAR recommendations.